Effective Binding of a Phosphatidylserine-Targeting Antibody to Ebola Virus Infected Cells and Purified Virions - S. D. Dowall; V. A. Graham; K. Corbin-Lickfett; C. Empig; K. Schlunegger; C. B. Bruce; L. Easterbrook; R. Hewson (Journal of Immunology Research)
Ebola virus is responsible for causing severe hemorrhagic fevers, with case fatality rates of up to 90%. Currently, no antiviral or vaccine is licensed against Ebola virus. A phosphatidylserine-targeting antibody (PGN401, bavituximab) has previously been shown to have broad-spectrum antiviral activity. Here, we demonstrate that PGN401 specifically binds to Ebola virus and recognizes infected cells. Our study provides the first evidence of phosphatidylserine-targeting antibody reactivity against Ebola virus.